The Sacrament of Penance: precedents of dispositions of the Third Council in Lima - Florez Davila, Gloria Cristina (2015)
Our article analyzes evolution of Catholicism in a wide chronological context that was given between the IV Council of Lima (1215) and the III Council of Lima (1582-1583). This study allows us to understand better the sacramental practice Pre-Tridentine and the important methods used in catechism, such as confession, penance and sermon. Later new conditions were given in societies of the XVI Century favoring a new pastoral, defined by the Council of Trent (1545-1563), and their interest for orthodoxy and orthopraxis encouraged a more important control and uniformity in the catechesis of the religious. Their aims were clearly demonstrated by dispositions of the Third Council of Lim (1582-1583), and as in other Councils, the penitential practice was based in the use of sermons, manuals of confession, catechism and sermonaries.